Design and investigation of a dual-layer grating coupler for efficient vertical fiber-chip coupling. (11th December 2018) - Yu, Jiyao; Yamada, Hirohito
Abstract: A novel dual-layer grating coupler was designed for efficient vertical coupling between a single-mode fiber and silicon nanowires, with characteristics of polarization diversity and both wavelength bands of 1.3 and 1.55  μ m. Theoretical analysis and two-dimensional finite-difference time-domain simulations were applied to verify the performance of the design. Optimized results show that the coupling efficiencies of a dual-port output of 41% (−3.87 dB) for transverse-electric polarization at 1.56  μ m, 32.88% (−4.83 dB) for transverse-magnetic (TM) polarization at 1.58  μ m, and 27.06% (−5.68 dB) for TM polarization at 1.32  μ m can be achieved. Dual-layer Fabry–Perot resonance was also investigated for high coupling efficiency.